The Effectiveness of Breakfast Education on EnergyIntake, Protein, Nutritional Status and LearningAchievement of Elementary School Children - Retno Dewi Noviyanti; Dewi Pertiwi Dyah Kusudaryati (Prosiding University Research Colloquium, 2022)
School children (7-12 years) are nutritionally vulnerable groups. Provision of nutrition with good and correct quality and quantity greatly influences the growth of school-age children. Breakfast has an important role in meeting energy and nutrient needs. These nutrients will affect nutritional status and can increase the concentration of learning. This research aims to analyze the effectiveness of education about breakfast on energy, protein, nutritional status and learning achievement of elementary school children. The study design was experimental randomized pretest-posttest control group design. The sample of this study was elementary students of students aged 9-12 years with a sample of 56 children who were chosen by simple random sampling at the Muhammadiyah Elementary School in Surakarta Special Program. The sample was divided into 2 groups, namely the treatment group (power point media and booklet) and the comparison group (booklet only). The intervention was carried out for 12 weeks. Paired t test and Wilcoxon test to analyze differences in energy intake, protein, nutritional status and learning achievement before and after intervention in each group. Mann Whitney test to analyze differences between groups. The results of this research was the mean nutritional status before 0.77 ± 1.60 and after 0.78 ± 1.62. The mean energy intake before 131.57 ± 54.15% and after 131.49 ± 53.21%. The mean protein intake before 112.45 ± 36.63% and after 112.39 ± 26.15%. The average learning achievement before 80.38 ± 8.25 and after 83.00 ± 4.95. Breakfast habits increased from 82.1% to 89.3%. Differences between groups for nutritional status data (p = 0.974), energy intake (p = 0.002), protein intake (p = 0.049), learning achievement (p = 0.001).The conclusion of this research was there were differences in energy intake, protein and learning achievement between intervention groups, but there were no differences in nutritional status between groups. Interventions in the treatment group were more effective than the comparison group.